Influence of School Infrastructures on Students’ Academic Performance in Public Senior Secondary Schools in Kogi State, Nigeria - OLOWONEFA, J, A. Ph.D; OGUNODE, N,. J (Researchparks Publishing, 2022)
School infrastructures are usually defined to include the site, the building and all unmovable structures in the school. The study shows how effective funding and maintenance of school infrastructures influence students’ academic performance. A descriptive survey research designed was used. The simple random sampling procedure was adopted. The population of this study consists of 56 principals and 3,394 teachers in public secondary schools in Kogi State. A questionnaire: Influence of School Infrastructures on Students’ Academic Performance (ISISAP) was used for data collection. Two research questions were answered and two hypotheses tested at 0.05 level of significance with the use of chi-square. Data were analyzed using simple percentage. The finding reveals that school infrastructures to a large extent influence students’ academic performance. However, there are problems encountered in the application of school infrastructures planning which include; involvement of non-educationist expert, shortage of professional literature for planning, engagement of large contractors in school infrastructures planning, poor maintenance of school infrastructures and poor maintenance approach as a result of inadequate inventories. This paper therefore recommends involvement of educational experts for school infrastructures planning, acquisition of professional text materials for school infrastructures planning by developing countries, engagement of smaller contractors in school infrastructures planning, application of well planned strategies by school managers and development of good planned approach by government and educational managers.